The Transformative Power of the EU-Ukraine DCFTA: Evidence from the Ongoing Deregulation Reform in Ukraine - Maryna Rabinovych (CES Working Papers, 2016)
The lack of genuine transformative power in the region was repeatedly distinguished as a major weakness of the Eastern Partnership (EaP) in Ukraine. However, the intensity and comprehensiveness of ongoing reform processes cause the need to revise the transformative power of the initiative in general and specific incentives in particular. Thus, the paper aims to assess the transformative power of the EU-Ukraine DCFTA, based on the evidence from the deregulation reform that represents an important prerequisite for the intensification of the EU-Ukraine economic relations. The study focuses on the general economic aspects of deregulation and combines 'black letter law' approach with an empirical insight into the reform's implementation. The results of the study show that the EU-Ukraine DCFTA holds significant transformative power with regard to the deregulation of Ukraine's economy and invite for further reconsideration of the EaP incentives' impact in target states.
Keywords: K0; 330; Eastern Partnership; DCFTA; EU-Ukraine Association Agenda; deregulation reform